Building Relationships in a Cold Climate: A Case Study of Family Engagement within an 'Edge of Care' Family Support Service. Issue 2 (17th November 2015) - Sen, Robin
Abstract : Drawing on a case study generated as part of a larger evaluation, this article explores engagement between one family and an 'edge of care' intensive family support service, within a cold climate of public spending cuts and rising numbers of children in care. The focus on engagement in the case study illustrates theories about relationship building at the 'edge of care': the importance of an empathic relationship; harnessing parents' agency for change while raising child welfare concerns; allowing parents space to maintain a positive self-conception of parenthood while supporting improvements; and engagement with family practices. The case study highlights that, despite the potential disciplinary aspects of intensive family support, the parents valued the 'edge of care' service because it provided them with the help they felt they needed, contrasting with their prior experience of statutory child welfare agency practice.